The Influence of Leadership and Work Motivation on Teacher’s Work Discipline - Pebrianti, Putri; Ahyani, Nur; Eddy, Syaiful (Yayasan Sembilan Pemuda Indonesia, 2024)
This study aims to analyze the influence of leadership and work motivation on teacher work discipline. This type of research is quantitative research. The sample of this research was 106 teachers of SD Negeri Gugus 1, Sungaiselan District. Data collection tool using a questionnaire. Data analysis using multiple regression test techniques. The results of the study stated that (1) there was a significant influence between leadership on the work discipline of SD Gugus 1 teacher in Sungaiselan District; (2) There is a significant influence between work motivation on the work discipline of SD Gugus 1 teachers in Sungaiselan District; (2) There is a significant influence of leadership and work motivation on the work discipline of SD Gugus 1 teachers in Sungaiselan District together by 94.2% and the remaining 6.8% is influenced by other factors not examined in this study.